USING META-PROGRAMMING, CONSTRAINT LOGIC PROGRAMMING AND APPROXIMATE REASONING FOR EXPERT SYSTEMS DESIGN - ROVENTA, EUGENE (International journal of general systems, 1999)
This paper presents an enhancement of the CARESS system-A Constraint Approximative Reasoning System Support-introduced in (Popescu and Roventa, 1994). CARESS is an experimental system with primarily two objectives: (1)knowledge representation and manipulation techniques and to implement them in PROLOG III, and (2) to develop a knowledge programming environment for building expert systems. We discuss here the use of meta-programming, constraint logic programming and approximate reasoning for the design of expert systems It has already been proven that meta-programming and logic programming are powerful techniques for expert system design. Fuzzy logic can be used to model one kind of uncertainty. Constraint logic programming is useful for dealing with the constraints given by operations using fuzzy sets.